Geographical distribution of Brucella melitensis inferred from rpoB gene variation - Tan, K.K.; Tan, Y.C.; Chang, L.Y.; Lee, K.W.; Nor'e, S.S.; Yee, W.Y.; Hoh, C.C.; AbuBakar, Sazaly (Journal of Infection in Developing Countries, 2017)
Introduction: Currently available tests have limitations for the identification of Brucella species and strains, and their genetic lineage. The genome sequence of the rpoB gene encoding the β-subunit of DNA-dependent RNA polymerase was investigated for its use in genotyping Brucella melitensis. Methodology: Complete rpoB gene sequences of globally distributed Brucella melitensis strains were analyzed. Single nucleotides polymorphisms (SNPs) of the rpoB gene sequences were identified and used to type Brucella melitensis strains. Results: Six DNA polymorphisms were identified, of which two (nucleotides 3201 and 558) were novel. Analysis of the geographical distribution of the strains revealed a spatial clustering pattern with rpoB type 1 representing European and American strains, rpoB type 2 representing European, African, and Asian strains, rpoB type 3 representing Mediterranean strains, and rpoB type 4 representing African (C3201T) and European (C3201T/T558A) strains. Conclusions: We report the discovery of two novel SNPs of rpoB gene that can serve as useful markers for epidemiology and geographical tracking of B. melitensis.